2012
DOI: 10.4028/www.scientific.net/amr.626.727
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Studies of Oxirane Ring Opening Reaction in Epoxidized Natural Rubber (ENR-50) by SnCl<sub>2</sub>.2H<sub>2</sub>O and the Formation of ENR/TiN Complex Hybrid

Abstract: Oxirane ring opening reaction of epoxidized natural rubber (ENR-50) is a promising method to produce hybrids or introduce reactive fillers into the polymers through the covalent bond. This paper reports the reaction between ENR-50 and SnCl2.2H2O under CO2environment. The complex formation is characterized via FTIR,1H,13C and119Sn NMR.1H NMR which displays deduction of methine proton integrals at δ 2.71 ppm implies the occurrence ring opening reaction. While13C NMR reveals new peaks which corresponds to Sn-C bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In ENR, the ring opening reaction of ENR with 50 mol % (i.e., ENR-50) was conducted in the presence of SnCl 2 ∙2H 2 O catalyst. The ENR/Sn complex hybrid was thereafter formed via insertion of SnCl 2 into the quaternary and methine carbon of ring-opened ENR molecules under CO 2 atmosphere [ 16 ]. Simultaneously, it was found that the ferric ion (Fe 3+ ) is one the most efficient metal ions to promote the crosslinking reaction of ENR molecules [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In ENR, the ring opening reaction of ENR with 50 mol % (i.e., ENR-50) was conducted in the presence of SnCl 2 ∙2H 2 O catalyst. The ENR/Sn complex hybrid was thereafter formed via insertion of SnCl 2 into the quaternary and methine carbon of ring-opened ENR molecules under CO 2 atmosphere [ 16 ]. Simultaneously, it was found that the ferric ion (Fe 3+ ) is one the most efficient metal ions to promote the crosslinking reaction of ENR molecules [ 17 ].…”
Section: Introductionmentioning
confidence: 99%